2016
DOI: 10.1080/00918369.2016.1174021
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Physical Health Conditions Among Lesbian and Bisexual Women: A Systematic Review of Population-Based Studies

Abstract: We conducted a systematic review to assess evidence for disparities for lesbian and bisexual women (i.e., sexual minority women [SMW]) in comparison with heterosexual women across a range of nine physical health conditions. Among the k = 11 studies meeting eligibility criteria, almost every comparison (i.e., heterosexual vs. (a) lesbian, (b) bisexual, or (c) both lesbian and bisexual women) was in a direction indicating SMW disparities. Despite limited power due to small samples of SMW, we found evidence of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 23 publications
4
52
0
2
Order By: Relevance
“…22 Reviews of the extant literature, however, also support an equivalent risk of hypertension and diabetes among lesbian, bisexual, and heterosexual women. 23,24 In contrast, population-based studies have shown higher rates of obesity among SMW, ages 50 and older, compared with heterosexual women. [23][24][25] Although older SMW consistently report poorer self-rated mental health and heightened physical disability relative to their heterosexual counterparts, 26,27 results of studies are equivocal in regard to sexual identity differences in self-rated physical health among older adult women living in the United States.…”
Section: Aging and Health Among Smwmentioning
confidence: 97%
“…22 Reviews of the extant literature, however, also support an equivalent risk of hypertension and diabetes among lesbian, bisexual, and heterosexual women. 23,24 In contrast, population-based studies have shown higher rates of obesity among SMW, ages 50 and older, compared with heterosexual women. [23][24][25] Although older SMW consistently report poorer self-rated mental health and heightened physical disability relative to their heterosexual counterparts, 26,27 results of studies are equivocal in regard to sexual identity differences in self-rated physical health among older adult women living in the United States.…”
Section: Aging and Health Among Smwmentioning
confidence: 97%
“…The IOM report 1 noted that lesbian and bisexual women are at greater risk of obesity, cardiovascular disease, and some types of cancer, and a systematic review has suggested that SMW report poorer health outcomes compared with heterosexual women. 25 A study of Washington state residents also found that lesbian and bisexual women were at greater risk for poor general health and experiencing physical limitations; bisexual women had greater odds of hypertension and diabetes compared with heterosexual women. 17 In another study, bisexual women reported more non-HIV-related health problems compared with heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
“…Lesbian and bisexual women report worse global ratings of physical health than heterosexual women [8]. They are less likely to have routine care and cancer screenings including mammography or cervical screenings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%